Flexible Removable Partial Denture Prosthesis: A Survey of Dentists' Attitudes and Knowledge in Greece and Croatia - Gregory Polyzois; Panagiotis Lagouvardos; Josip Kranjčić; Denis Vojvodić (University of Zagreb. School of Dental Medicine, 2015)
Purpose: The aim of this study was to investigate through a questionnaire the knowledge, attitudes and possible differences in the use of flexible RPDPs among dentists in Greece and Croatia. Material and Methods: A questionnaire of 16 questions was originally created in English, translated into Greek and Croatian language following a two way translation and tested for apprehension, precision, clarity and homogeneity by a number of native English speaking Greek and Croatian dentists. Following the necessary corrections, the questionnaires replicated in two online surveys and their addresses with an informed consent were sent by emails to nearly 4000 dentists in each country to participate. Collected data were analyzed by chi-square tests at a= .05 level of significance. Results: 378 dentists from Greece and 304 from Croatia participated in the study. 137(36.2%) dentists from Greece and 56(18.4%) from Croatia provided flexible RPDPs to their patients. Statistical analysis for all providers indicated no significant difference between genders (P>.05), significant differences between age groups (P<.01), years of practice (P<.05), specialization (P <.001), and instruction on flexible prostheses (P <.001). The analysis between the two countries showed differences for gender and age groups (P<.01) but no differences between experienced, specialized or instructed groups (P >.05). Conclusion: The survey indicated differences between the two countries in the percentages of dentists using, selecting and providing RPDPs for their patients. Practitioners' age, years in practice and instruction were associated with the provision of the prostheses, while comfort, esthetics and cost were the reasons for deciding to use the flexible RPDPs. Conclusion: Although dentists are not educated in their schools about flexible RPDPs, almost a third of them offer this treatment to their patients. Long term success of these devices depends on clinical education, more experience and definitely more research.